Remote Patient Monitoring System Using WLAN-Enabled Mobile Phones in Tikrit Educational Hospital - Hussein, Harith A. (2009)
This study aims to provide an applicable simulation on implementing a Remote Patients Monitoring System Via WLAN to improve the existed system in the Educational Hospital of Tikrit, Iraq, and gives the hospital staff the ability to access the vital information of the patients who are in emergency cases through the internet by using WLAN-enabled mobiles. In this study, the process of patient diagnosis will be shown in order to enable remote access of the data stored and updated in the Medical Monitoring Center under critical environments which surrounding the territory of the city. In addition to that, there will be a justification of choosing WLAN among the other technologies.